FACTOR OF INCREASING OCCUPANCY AT THE HOTEL COMFORTA DUMAI RIAU PROVINCE - Rias Rekha Nita; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Response in the world of tourism is the opinion or point of view of visitors and tourists in understanding a tourist destination. This research was conducted at the Comforta Hotel Dumai located at jl. jend. Sudirman no. 58, Dumai- Riau- Indonesia. This study aims to determine the factors and efforts to improve occupancy at the Comforta Dumai hotel. This study uses a qualitative descriptive method to process data obtained in the field through interviews, observation and documentation. all information collected and studied so that it becomes a complete unit (Sugiono. 2000). Meanwhile, for the sample in the study there were seven keys information persons. Data collection techniques used were observation, interviews, and documentation. Based on the results of research that has been carried out, the occupancy increasing factors at the Hotel Comforta Dumai are the location factor and the Promotion Factor and efforts to increase the occupancy of the Hotel Comforta Dumai are making advertisements, promoting hotel programs and hotel facilities. Keywords: Factors, Occupancy, Sales marketin.,